(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The first attempts by man to convey information using text and pictures go back to ancient times. The combination of images and text is typical for most monuments of ancient civilizations in the World. Among the most striking monuments of ancient writing, including elements of pictorial writing and text, it should be noted wall writings and drawings in ancient Egyptian tombs, which form a single textual work. In society individuals communicate in different ways, it is important to be aware of the different modes used in communication to fully understand the meanings that are being conveyed. These can be broken down into five categories: linguistic, visual, gestural, spatial. The linguistic mode focuses on the meaning of written or spoken language in communication.